2004
DOI: 10.1046/j.0305-182x.2003.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

The attitude of complete denture wearers towards denture adhesives in Istanbul

Abstract: Turkey SUMMARY The purpose of using denture adhesives is to subjectively benefit denture-wearers with improved fit and comfort of their dentures and to improve their chewing ability and confidence. The purpose of this study was to investigate the approach and thought of complete denture wearers to denture adhesives and to see why they had tried denture adhesive, and their reasons for its current use or non-use through a questionnaire. One hundred and fifteen patients attending the Marmara University, Dental Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 7 publications
3
48
4
Order By: Relevance
“…There would be little, or no difference in school education of both countries concerning denture adhesive. The results support the same opinion reported by Ozan et al, 14 which should be taught more intensively at dental schools.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…There would be little, or no difference in school education of both countries concerning denture adhesive. The results support the same opinion reported by Ozan et al, 14 which should be taught more intensively at dental schools.…”
Section: Discussionsupporting
confidence: 82%
“…13 Several reports noted that the main reasons for the use of denture adhesive are to improve fit, comfort, chewing ability, and also to improve patient confidence in wearing dentures. 5,14 Fifteen per cent of denture wearers in the US used denture adhesives in 1980. 15,16 Wilson et al 17 reported that 30 per cent of denture wearers used, or had used, denture adhesive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The awareness toward denture adhesive is lower compared to previous studies as 100% reported by G. L. Polyzois and 87% by Ӧzcan et al 31,32 The purpose of denture adhesives is to benefit denture wearers with a more appropriate fit and comfort and improve their chewing ability and confidence. 32 However, only 23.1% of the patients used denture adhesive in this study. 40.6% of patients used denture adhesive for better denture retention which is relatively similar to previous study by G. L. Polyzois and C. de Baat.…”
Section: Discussioncontrasting
confidence: 45%
“…Despite the more or less restraining attitude of dentists towards denture adhesives, it has been shown that a substantial proportion of denture wearers (7-33%) had tried denture adhesives in the past or were regular users currently [5,23]. Responses of patients to questions regarding satisfaction, retention, and eating and masticatory performance of complete dentures demonstrated a subjec-tive improvement when using a denture adhesive [1,16,25,29].…”
Section: Introductionmentioning
confidence: 99%